Analysis of Market Structure, Behavior and Performance at the Manding Leather Industry Center of Bantul Yogyakarta - Suripto Suripto; Isna Tri Wulandari; Ignatius Abasimi (Journal of Asset Management and Public Economy (JAMPE), 2022)
Bantul Regency has the largest and only leather product industry center in the DIY Province. Marketing at the center of the leather industry is competition between each leather producer. This is a crisis problem and must find a solution to overcome it. The analysis that can be used to determine the marketing system is SCP (Structure-Conduct-Performance) analysis. This research was conducted at the leather industry center in Manding, Sabdodadi, Bantul district, Bantul, Yogyakarta Special Region. This study aims to determine the structure, behavior and market performance of the leather industry center in Manding. The method used by the researchers in this study used primary data from leather craftsmen and secondary data (BPS) as well as interviews and filling out questionnaires. The results showed that the structure of the leather market in Manding was an oligopoly with a CR4 calculation of 70.14%. For the market behavior of the leather industry in Manding with the CLR calculation, it is included in the labor-intensive industry class with the calculation results below 20% and market performance seen from the PCM obtained an average of 0.53%. With the largest PCM is 0.95% but the largest PCM does not become the largest market share (MS) means the benefits seen from PCM do not affect the market share.